An Survival Genius Analysis Faced by The Main Characters in All Is Lost Movie - Bangi Kaa, Dewi Yanti; Utami , Ni Made Verayanti (Journal of Language and Applied Linguistics, 2025)
This research deals with the psychological aspects of human behavior found in “All Is Lost” movie by Jeffery McDonnell Chandor. This research aims to analyze behavior and identify the psychological aspects of the main character in “All Is Lost” Movie. The data are taken from. Scenes of the movie. The theory used in this paper is the theory of the self-defense mechanism by Sigmund Freud's semium (2006), Anna Freud (1936), and the theory of personality structure by Sigmund Freud in semium (2006). This study used the descriptive qualitative method. The result of this study represented the fourth type of psychological aspect of the main character found in the movie. The dominant type that appears in this research is survival genius. In this study, the data were collected using the observation method. The data were observed using note-taking techniques to identify and analyze the data.